Vertical Integration Market Analysis of Palm Oil Fresh Fruit Bunches in West Sumatera, Indonesia - Nesti, Lisa; Tan, Firwan; Ridwan, Endrizal; Ampuh Hadiguna, Rika (International Journal of Engineering and Technology, 2018)
This study aims to examine whether there is asymmetric information on the vertical integration market in palm oil Fresh Fruit Bunches (FFB) in West Sumatera using Error Correction Model (ECM) and analyze the factors causing price inefficiency of oil palm in West Sumatera. The result obtained the change in price of FFB of palm oil of sales realization at agent level, sales realization of export  price of crude palm oil (CPO), and sales realization of export  price of kernel have positive effect on sales realization at smallholder price of FFB  level and  Error Correction Term (ECT) value is negative and significant at 5%  of real level, which states that in the short and long run, the free variables used significantly influence the sales realization at smallholder price of  FFB of palm oil  level. Exporter of CPO  is one actor involved in it who has dominant power in influencing the selling price of FFB so that they can manage the selling price of FFB farmers as a producer of palm oil, this is the cause of inefficiencies in the vertical integration market